THE ANALYSIS OF UNSAFE DRIVING IN JEEP CAR DRIVER AT LAVA TOUR AREA OF MERAPI VOLCANO - Risdha Ayu Maruti; Muchamad Rifai; Helfi Agustin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Merapi Lava Tour is a tourist destination to enjoy the natural beauty of Merapi with a jeep. Jeep accidents on Merapi Lava Tour have occurred several times, killing at least two passengers. The purpose of this study is to analyze the unsafe driving behavior of Merapi Lava Tour jeep drivers. The type of the research is qualitative research with purposive sampling technique, involving 9 informants that consist of 4 jeep drivers, the chairman of the association and 4 jeep passengers. The data were collected through interview and observation. The research site was at Merapi Lava Tour area. The result of the research suggests that the drivers’ knowledge about safety driving is good and they also have positive driving attitudes. However, in practice, there are drivers who violated the regulation and committed unsafe behavior while driving. Merapi Lava Tour has been equipped with accident insurance, Standard Operating Procedure (SOP) and Personal Protective Equipment (PPE) for jeep drivers, but there are also still inadequate facilities, i.e. first aid kit that has not been evenly distributed and training on safety driving that is not available for all drivers yet.Wisata Lava Tour Merapi adalah tujuan wisata untuk menikmati keindahan alam Merapi dengan jeep. Kecelakaan jeep di wisata Lava Tour Merapi telah terjadi beberapa kali, yang menyebabkan setidaknya dua penumpang meninggal dunia. Tujuan dari penelitian ini adalah untuk menganalisis perilaku tidak aman pengemudi jeep Lava Tour Merapi. Tipe penelitian ini jenis penelitian kualitatif dengan teknik Purposive sampling, terdiri dari 9 informan yaitu pengemudi jeep, ketua asosiasi jeep, dan penumpang jeep. Metode pengumpulan data dengan wawancara dan observasi. Lokasi penelitian di kawasan Lava Tour Merapi. Hasil penelitian menunjukkan bahwa pengetahuan pengemudi sudah baik terkait mengemudi dan bersikap positif tetapi dalam praktiknya ada pengemudi yang melanggar dan berperilaku tidak aman saat mengemudi. Lava Tour Merapi telah dilengkapi asuransi kecelakaan, Standar Operasional Prosedur (SOP) dan Alat Pelindung Diri (APD) untuk mengendarai jeep, tetapi ada fasilitas yang tidak memadai yaitu kotak P3K belum merata dan belum ada pelatihan keselamatan mengemudi jeep.